The image of a religious and mystical scholar in Usman Kochkar’s drama "Imam Bukhari" - Osomiddinova Gulkhayo (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article analyzes the drama “Imom Buxoriy” by Usmon Qo‘chqor. The study focuses on the artistic interpretation of Imam al-Bukhari as a religious and Sufi scholar within the work. It examines the protagonist’s pursuit of knowledge, spiritual endurance, faith, and moral purity through literary analysis. The paper also highlights the central idea of the drama, which revolves around knowledge, truth, and faith, as well as the core conflict built on the opposition between enlightenment and ignorance. Furthermore, the system of characters, Sufi concepts, dramatic techniques, and the educational significance of the work are explored from a literary-critical perspective. As a result, the drama is evaluated as an important example of Uzbek historical dramaturgy.